Comparison of synthetic and low-cost natural zeolite for bio-oil focused pyrolysis of raw and pretreated biomass. (1st September 2021) - Khan, Shoaib Raza; Zeeshan, Muhammad; Ahmed, Absar; Saeed, Sara
Abstract: Acid-pretreatment of rice straw (RS) and its subsequent pyrolysis with and without natural zeolite (NZ) and HZSM-5 catalysts were investigated and compared comprehensively. Acid-washing eluted 96% K, 74.73% Ca, 94.78% Mg and 98.33% Na metals from RS besides improving its higher heating value (HHV) and relative content of lignocellulose. Oxygenates reduction of 25.84% along with 12 folds increase in levoglucosan was observed during pyrolysis of washed-RS (W-RS) compared to raw-RS (R-RS). Oxygenates transformation into hydrocarbons was significantly promoted with both catalysts. The selectivity of most valuable aromatic hydrocarbons e.g benzene, toluene and xylene (BTX) of HZSM-5 was superior to that of NZ in either of RS with the highest selectivity of 16%(B), 22%(T) and 30%(X) in W-RS/HZSM-5 due to its higher total pore volume, surface area and lower acidity and controlled reforming reactions. NZ selectivity for BTX was also improved from 7.69%, 13.04% and 8.69% during R-RS/NZ to 10.52%, 15.78% and 21.05% for W-RS/NZ, respectively. Moreover, HHV of W-RS/NZ bio-oil was 26.32 MJ/kg whilst that of W-RS/HZSM-5 oil (30.95 MJ/kg) was highest among all. Besides, physical characteristics of bio-oil including density, flash points and pour points were improved with both catalysts in the case of W-RS compared to R-RS. Graphical abstract: Image 1 Highlights: Acid washed rice straw (W-RS) had better fuel qualities than raw rice straw (R-RS). Natural zeolite (NZ) had lower surface area, SiO2/Al2O3 ratio and higher pore size. HZSM-5 transformed more oxygenates into hydrocarbons than NZ in both R-RS and W-RS. Selectivity of benzene, toluene and xylene in W-RS/NZ was superior to R-RS/NZ. W-RS/HZSM-5 bio-oil had better physical properties compared with that of W-RS/NZ.